The "sufferings" of the crime of torture (2014)
The Colombian Constitutional Court abolished the word “severe” from the legal definition of torture in 2005. As a result of that decision, torture was formulated as “physical or mental suffering” in Colombian criminal law. Nevertheless, the actual legal d